Genetic transformation of Primula sieboldii using Agrobacterium rhizogenes and whole-plant regeneration from transgenic hairy roots - Gad, Karol; Huu, Cuong Nguyen; Plaschil, Sylvia; Kappel, Christian; Lenhard, Michael (Frontiers in Plant Science, 2025)
Primula sieboldii E. Morren is a widely cultivated ornamental plant with horticultural and pharmacological value. However, the lack of a developed transformation system has limited genetic studies and biotechnological applications of this species. In this study, we established a transformation method using Agrobacterium rhizogenes for the genetic manipulation of Primula sieboldii. The protocol consists of two stages: initial hairy root transformation and subsequent whole-plant regeneration from transgenic hairy roots through somatic embryogenesis. Comprehensive molecular analyses confirmed the stable integration and expression of various transgenes from the root-inducing (Ri) plasmid and the binary vector carrying the RUBY reporter in independent transgenic lines, as well as the stable germline transmission of the transgene to progeny. The protocol is effective, with 5% of treated explants successfully forming transformed hairy roots expressing the RUBY reporter, from which transgenic plants were regenerated. The established method provides a valuable tool for genetic and molecular studies of heterostyly and the self-incompatibility system in the genus Primula, while also offering practical applications in molecular breeding and plant biotechnology. Additionally, hairy root cultures provide a platform for metabolic engineering and the exploration of biologically active secondary metabolites with pharmacological applications.